2007
DOI: 10.3349/ymj.2007.48.4.619
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of AmBisome® to Amphotericin B for Treatment of Systemic Candidiasis in Very Low Birth Weight Infants

Abstract: PurposeAmphotericin B is considered the treatment of choice for systemic candidiasis, but adverse effects may limit its use. An alternative option for the treatment of candidiasis includes lipid preparations of amphotericin B. This study investigated the safety and efficacy of AmBisome®, a lipid formulation of amphotericin B containing liposomal structures, for the treatment of systemic candidiasis in very low birth weight infants (VLBWI).Materials and MethodsData from 26 VLBWI treated with AmBisome® in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The two studies that compared DAMB and lipid formulations showed no difference in overall survival rate or in the time of resolution of fungaemia [41,42]. One of them used DAMB group as historical control [42]. Overall neonatal survival rate in invasive candidiasis treated with DAMB alone in studies published after 1997 varies from 74 to 94% (see Table 2 [21] showed that treatment with high doses of LAMB is effective and well tolerated with an eradication rate of 95%.…”
Section: Deoxycholate Amphotericin Bmentioning
confidence: 96%
See 3 more Smart Citations
“…The two studies that compared DAMB and lipid formulations showed no difference in overall survival rate or in the time of resolution of fungaemia [41,42]. One of them used DAMB group as historical control [42]. Overall neonatal survival rate in invasive candidiasis treated with DAMB alone in studies published after 1997 varies from 74 to 94% (see Table 2 [21] showed that treatment with high doses of LAMB is effective and well tolerated with an eradication rate of 95%.…”
Section: Deoxycholate Amphotericin Bmentioning
confidence: 96%
“…Some studies used combination therapy with flucytosine (5-FC) or added fluconazole, which may have influenced the effect of therapy. The two studies that compared DAMB and lipid formulations showed no difference in overall survival rate or in the time of resolution of fungaemia [41,42]. One of them used DAMB group as historical control [42].…”
Section: Deoxycholate Amphotericin Bmentioning
confidence: 98%
See 2 more Smart Citations
“…Data are limited in standard dosing, starting with Fungal infections are associated with the greatest decrease (50%) in platelet counts, similar to gram-negative infections (Guida, 2003) the highest safe dose on day 1 of treatment, and use with prompt CVC removal with fungemia. A-II evidence supports AmB deoxycholate starting at 1 mg/kg per day, with a recent study demonstrating safety when increasing up to 1.5 mg/kg if needed 32 . Lipid preparations need a similar approach, starting at 5 mg/kg so underdosing does not affect efficacy, and one study has examined increasing to 7 mg/kg 33,34 .…”
Section: Treatment Of Invasive Fungal Infectionsmentioning
confidence: 99%